Performance analysis for producer mobility in named data networking - Azamuddin, Wan Muhammad Hazwan Azamuddin; Mohd Aman, Azana Hafizah; Sallehuddin, Hasimi; Attarbashi, Zainab; Zhang, Wenhua; Hassan, Suhaidi (Semarak Ilmu, 2024)
The influence of producer mobility on Named Data Networking (NDN) networks in dynamic networking environments is amplified, hence necessitating an escalation in the demand for performance analysis. When producers transition between different sites or nodes relocation, there is a significant increase in packet loss. Consequently, the present work centers on conducting experiments and evaluating producer mobility by utilizing the Hybrid Indirection Method (HIM) to mitigate the effects of signalling cost on the handoff procedure. This study aims to analyze the effects of producer mobility, specifically focusing on two critical factors: handoff signaling cost and packet data ratio. The data gathered from the study provide significant insights into the benefits and challenges related to producer mobility. This research paper comprehensively investigates producer mobility within the network simulator ns3 framework. The findings demonstrate a notable enhancement achieved by the HIM technique, resulting in substantial improvements in handoff signaling cost and packet data ratio.